Malaysian Indian Students' Attitude, Awareness And Practice Of Indian Traditional Knowledge For Sustainability - Marimuthu, Nagamah (2012)
The purpose of the study was to investigate the Form Four Malaysian Indian science stream students‟ attitude towards science and awareness of the relevance of science and their parents‟ views on them. A QUAN-Qual mix-method model with a survey and interview method was used to design and analyze the research. The data collection for the survey method consisted of two sets of questionnaires. The samples for the study consisted of 80 males and 80 females with equal number of urban and rural students and their parents.